Gender hierarchy in the Qurʼān medieval interpretations, modern responses - Bauer, Karen (Cambridge studies in Islamic civilization, 2015)
"This book explores how medieval and modern Muslim religious scholars ('ulamā') interpret gender roles in Qur'ā;nic verses on legal testimony, marriage, and human creation. Citing these verses, medieval scholars developed increasingly complex laws and interpretations upholding a male-dominated gender hierarchy; aspects of their interpretations influence religious norms and state laws in Muslim-majority countries today, yet other aspects have been discarded entirely. Karen Bauer traces the evolution of their interpretations, showing how they have been adopted, adapted, rejected, or replaced over time, by comparing the Qur'ān with a wide range of Qur'ānic commentaries and interviews with prominent religious scholars from Iran and Syria. At times, tradition is modified in unexpected ways: learned women argue against gender equality, or Grand Ayatollahs reject sayings of the Prophet, citing science instead. This innovative and engaging study highlights the effects of social and intellectual contexts on the formation of tradition, and on modern responses to it"--